The relationship between parenting attitudes, negative cognition, and the depressive symptoms according to gender in Korean adolescents. Issue 1 (December 2016) - Park, Subin; Kim, Bung-Nyun; Park, Min-Hyeon
Abstract Background Parenting style is one potential contributor to the development of adolescents' cognitions, self-esteem and emotional problems. This study examined the relationship between maternal parenting attitudes and adolescents' negative cognitions, and depressive symptoms according to gender. Methods A total of 401 middle and high school students were recruited (i.e. 221 males and 180 females; mean age, 13.92 ± 1.31 years). The Maternal Behavior Research Instrument assessed maternal parenting attitudes. Analyses examined the relationship between parenting attitudes and affective symptoms, with self-esteem and negative automatic thoughts as mediators of these relations. Results Maternal rejecting attitudes were positively associated with depressive symptoms via increasing negative autonomic thoughts and decreasing self-esteem among female adolescents. Among male adolescents, maternal rejecting attitudes were associated with low self-esteem, but they were not associated with depressive symptoms. Conclusions Maternal parenting has a larger impact on the emotional adjustment of females compared to males. Interventions to increase self-esteem and correct negative cognitions may be helpful for depressed female adolescents, specifically for those whose mothers are rejecting.